Psychedelic resting-state neuroimaging: A review and perspective on balancing replication and novel analyses. (July 2022) - McCulloch, Drummond E-Wen; Knudsen, Gitte Moos; Barrett, Frederick Streeter; Doss, Manoj K.; Carhart-Harris, Robin Lester; Rosas, Fernando E.; Deco, Gustavo; Kringelbach, Morten L.; Preller, Katrin H.; Ramaekers, Johannes G.; Mason, Natasha L.; Müller, Felix; et al.
Abstract: Clinical research into serotonergic psychedelics is expanding rapidly, showing promising efficacy across myriad disorders. Resting-state functional magnetic resonance imaging (rs-fMRI) is a commonly used strategy to identify psychedelic-induced changes in neural pathways in clinical and healthy populations. Here we, a large group of psychedelic imaging researchers, review the 42 research articles published to date, based on the 17 unique studies evaluating psychedelic effects on rs-fMRI, focusing on methodological variation. Prominently, we observe that nearly all studies vary in data processing and analysis methodology, two datasets are the foundation of over half of the published literature, and there is lexical ambiguity in common outcome metric terminology. We offer guidelines for future studies that encourage coherence in the field. Psychedelic rs-fMRI will benefit from the development of novel methods that expand our understanding of the brain mechanisms mediating its intriguing effects; yet, this field is at a crossroads where we must also consider the critical importance of consistency and replicability to effectively converge on stable representations of the neural effects of psychedelics. Graphical Abstract: ga1 Highlights: Psychedelic resting-state brain imaging has grown immensely over the past decade. To date, forty-two papers from seventeen unique datasets have been reported. Variations across the field in data processing and analysis limit replicability. An alignment in analysis methods is timely given the description of recent novel datasets. This paper offers guidelines to balance novel methods and replication in the field.